Study of nickel coating on clay ceramic body / Saidatulakmar Shamsuddin ... [et al.] - Shamsuddin, Saidatulakmar; Wanik, Baharuddin; Mohd Noor, Ahmad Fauzi; Ahmad, Zainal Ariffin (Universiti Teknologi MARA, Perlis, 2005)
Clay based ceramic body is successfully coated with nickel using a technique of electroplating. The prerequisite is to convert the surface of the ceramics into electrically conducting state. This can be done through the sensitization step followed by nucleation step and electroless plating process. For this study, the parameters for the sensitization step, nucleation step and the electroplating process are fixed, while changing the parameters for the electroless plating process. Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD) studies was employed to examine the quality of the coating. Results show that coating of Nickel was affected by duration and temperature of electroless plating.